Performance comparisons of current metaheuristic algorithms on unconstrained optimization problems - Can, Umit; Alatas, Bilal (International University of Sarajevo, 2017)
Nature-inspired metaheuristic algorithms have been recognized as powerful global optimization techniques in the last few decades.Many different metaheuristic optimization algorithms have been presented and successfully applied to different types of problems. In this paper; seven of newest metaheuristic algorithms namely, Ant Lion Optimization, Dragonfly Algorithm, Grey Wolf Optimization, Moth-Flame Optimization, Multi-Verse Optimizer, Sine Cosine Algorithm, and Whale Optimization Algorithm have been tested on unconstrained benchmark optimization problems and their performances have been reported. Some of these algorithms are based on swarm while some are based on biology and mathematics. Performance analysis of these novel search and optimization algorithms satisfying equal conditions on benchmark functions for the first time has given important information about their behaviors on unimodal and multi-modal optimization problems. These algorithms have been recently proposed and many new versions of them may be proposed in future for efficient results in many different types of search and optimization problems.
Keywords: Global Optimization; Metaheuristic Algorithms; Performance